Social aspects of urban development a case study of the pattern of urban development in the developing countries - Kopar?dekara, Hemacandra Day?ar?nava. (Bombay Popular Prakashan, 1986)
Study with reference to Maharashtra, India.
Includes index.
Bibliography: p. 377-387.
Keywords: Urbanization -- Case studies. -- India -- Maharashtra; Urbanization -- Case studies. -- India